Cloning of a temperature-regulated gene encoding a chloroplast omega-3 desaturase from Arabidopsis thaliana. - Gibson, S (1994)
Previous genetic evidence suggested that the fad8 and fad7 genes of Arabidopsis thaliana encode chloroplast membrane-associated omega-3 desaturases. A putative fad8 cDNA was isolated by heterologous hybridization using a gene encoding an endoplasmic reticulum-localized omega-3 desaturase (fad3) as a probe. The cDNA encodes a protein of 435 amino acid residues with a molecular mass of 50,134 D. Constitutive expression of the cDNA in transgenic plants of a fad7 mutant resulted in genetic complementation of the mutation, indicating that the fad7 and fad8 gene products are functionally equivalent. Expression of the fad8 cDNA in transgenic plants often resulted in the co-suppression of both the endogenous fad7 and fad8 genes in spite of the fact that these two genes share only about 75% nucleotide identity. In contrast to all other known plant desaturases, including fad7, the steady-state level of fad8 mRNA is strongly increased in plants grown at low temperature. This suggests that the role of fad8 is to provide increased omega-3 desaturase activity in plants that are exposed to low growth temperature. The fad8-1 mutation created a premature stop codon 149 amino acids from the amino-terminal end of the fad8 open reading frame, suggesting that this mutation results in a complete loss of fad8 activity.